USIA DAN PENGALAMAN MENGAJAR TERHADAP TEACHER EFFICACY DI SEKOLAH DASAR DENGAN KURIKULUM 2013 - FITRI LESTARI ISSOM; DEFI AMELIA (Journal of Research and Measurement in Psychology, 2015)
Age and teaching experience are part of the factors that affect teacher efficacy. This study aims to determine the effect of age and teaching experience on teacher efficacy in elementary school teachers who teach using Curriculum 2013. The number of samples in this study were 83 teachers who teach using the 2013 curriculum in North Jakarta. This research uses quantitative method with psychology scale. The preferred scale used to measure teacher efficacay seen from the age and experience of teaching teachers is Teacher Sense of Efficacy Scale (TSES). Data processing methods used in testing the research hypothesis is by multiple regression analysis. The results of this study indicate that there is a significant effect of age and teaching experience on teacher efficacy in elementary school teachers in North Jakarta with 0,018 (<0.05). The resultant effect 90.5 % Influenced beyond age and teaching experience.